Phytoremediation of Cr(VI) from Aqueos Solution by Pistia stratiotes L.: Efficiency and Kinetic Models - Haeril, Haeril; Sawali, Fikrah Dian Indrawati; Afandy, Moh Azhar (Jurnal Teknik Kimia dan Lingkungan, 2024)
Phytoremediation utilizes metal-trapping plants to recover water as the main source of contamination, Pistia Stratiotes L. is a hyperaccumulator plant that is considered capable of reducing hexavalent chromium levels in wastewater. This is evidenced by the results obtained on each of the variables investigated, namely the effect of contact time and the number of plants. Where, the effect of contact time on the most optimal reduction in hexavalent chromium concentration on day 10 is 22.55 mg/ L with an efficiency value of 54.89 %. While the effect of the number of plants on the reduction in the most optimal metal concentration was found in the first reactor with the number of plants 4, chromium concentration was 23.16 mg/ L with an efficiency value of 54.89%. This means that the longer the phytoremediation process will affect the decrease in chromium levels in waste samples but has no effect on the number of plants used if the plant mass is not calculated before treatment. The recommended kinetic models for phytoremediation systems using P. Stratiotes L plants are Richard's Pseudo First Order and Pseudo Second Order. However, when viewed from the prediction value and experimental data, Pseudo Second Order Kinetic Models are considered suitable to describe the phenomenon that occurs in this study, with an SSE value of 1.0042 and a reaction rate constant of 1.1662 day-1 to 1.5623 day-1.